Regulation of erythrocyte antioxidant enzyme activities in athletes during competition and short-term recovery - Tauler, P.; Gimeno, I.; Aguilo, A.; Guix, M. P.; Pons, A. (Pflügers Archiv - European Journal of Physiology, 1999)
We have determined "in vivo" the influence of strenuous prolonged exercise and short-term recovery on erythrocyte antioxidant enzyme activities. We have also determined the "in vitro" effects of the xanthine/xanthine-oxidase-generating superoxide anion system on catalase activity in haemolysed erythrocytes. Haematological parameters and erythrocyte superoxide dismutase (SOD), glutathione peroxidases and catalase activities were measured in nine healthy duathlon athletes under basal conditions, at the finish of a competition and after 1 h of recovery. We also measured catalase activity in haemolysed erythrocytes--obtained from four overnight-fasted well-trained sportsmen before and after an 80% submaximal exercise test on a cycle-ergometer--prior to and after incubation for 3 min with the superoxide-anion-generating system. Duathlon competition and/or short-term recovery produced a slight haemolysis and increased the activity of catalase and peroxidases but not SOD enzymes. The observed changes in catalase activity were mimicked "in vitro" by the superoxide-anion-generating system.